O-03 Working in co-production: Creative approaches to advance care planning with people excluded by identity, culture, ethnicity and race. (19th November 2022) - Jerwood, Jed; Allen, Gemma
Abstract : Background: The COVID-19 pandemic highlighted the health inequalities experienced by people from Black, Asian and minority ethnic people and communities in the UK (Chidiac, Feuer, Flatley, et al., 2020. Palliat Med. 34:1241). There is a lack of understanding of the needs of different BAME communities in the palliative care workforce (Hussain, Koffman & Bajwah, 2021. Palliat Med. 35:810). Consequently, people from BAME communities have less access to advance care planning (ACP). Aim(s): The research project had two main aims: To explore whether our equity-focused, arts-based approach to advance care planning (the No Barriers Here model) could be further developed to gain better understanding of the needs and experiences of people excluded by identity, ethnicity, culture and race in the locality. To take this understanding and develop an education programme for healthcare professionals to improve cultural competence in the workforce. Methods: A co-production group was formed including members of different communities often excluded by identity, culture, ethnicity or race. The co-production group supported the development of the model and recruitment of participants into three cohorts and each cohort took part in three arts-based ACP workshops. The data from the workshops were analysed using reflexive thematic analysis (Braun, Clarke, 2014. Int J Qual Stud Health Well-being. 9:1; Braun & Clarke, 2006. Qual Res Psychol. 3:77) and the findings used to inform the development of an education programme. Results: Key themes are developed within the data analysis and will be presented in the session (data analysis is currently ongoing at the time of writing). Conclusions: The conclusions will be presented at conference. Early indications highlight that adoption of co-production methods and an equity-focused, arts-based approach to advance care planning offer communities often excluded by identity, culture, ethnicity and race an opportunity to explore and share what matters most at the end of life, what barriers are experienced in accessing care and what services and support are available. The method appears to amplify voices of communities which organisations and healthcare professionals sometimes struggle to hear. A film about the No Barriers Here study with people excluded due to identity, culture, ethnicity and race is available at: https://youtu.be/G-ToRCT3UiU